Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Get quick and reliable solutions to your questions from a community of experienced professionals on our platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

Prove the following relations: 1) (1 - cos²A) (1 + tan²A) = tan²A​

Sagot :

Step-by-step explanation:

(1 - cos²A)(1 + tan²A) = tan²A

1 + tan²A - cos²A - cos²A · tan²A = tan²A

1 + tan²A(1 - cos²A) - cos²A = tan²A

1 - cos²A + tan²A(sin²A) = tan²A

sin²A + tan²A(sin²A) = tan²A

sin²A (1 + tan²A) = tan²A

sin²A (sec²A) = tan²A

sin²A (1/cos²A) = tan²A

(sin²A)/(cos²A) = tan²A

tan²A = tan²A → Proved